From the “Judicialization of Politics” to the “Politicization of Justice” in the UK and Switzerland - Della Torre, Lucia (Border Crossing, 2016)
Not very long ago, scholars saw it fit to name a new and quite widespread phenomenon they had observed developing over the years as the “judicialization” of politics, meaning by it the expanding control of the judiciary at the expenses of the other powers of the State. Things seem yet to have begun to change, especially in Migration Law. Generally quite a marginal branch of the State’s corpus iuris, this latter has already lent itself to different forms of experimentations which then, spilling over into other legislative disciplines, end up by becoming the new general rule. The new interaction between the judiciary and the executive in this specific field as it is unfolding in such countries as the UK and Switzerland may prove to be yet another example of these dynamics.